Case report and literature review: PET/CT in the evaluation of response to treatment of liver metastasis from colorectal cancer with DEBIRI-TACE - Jin, Lan; Hu, Wuyun; Li, Teng; Sun, Honghua; Kang, Dongxu; Piao, Longzhen (Frontiers in Oncology, 2023)
Background: Irinotecan-loaded drug-eluting beads transarterial chemoembolization (DEBIRI-TACE) is a safe and effective therapeutic option for unresectable colorectal liver metastases (CRLM). The evaluation of treatment response after DEBIRI-TACE is very important for assessing the patient’s condition. At present, the Response Evaluation Criteria in Solid Tumors (RECIST) with the tumor size obtained by CT and/or MRI and PET Response Criteria in Solid Tumors (PERCIST) based on fluorodeoxyglucose-positron emission tomography/computed tomography (FDG PET/CT) are used for evaluating the response to therapy of solid tumors; however, their value in the assessment of treatment response after DEBIRI-TACE remains unclear. Case presentation: A 52-year-old male with unresectable simultaneous CRLM was treated in the Affiliated Hospital of Yanbian University with DEBIRI-TACE combined with systemic chemotherapy and targeted therapy. Carcinoembryonic antigen levels decreased by 82.50% after 27 days of treatment. At 6 weeks post-surgery, FDG-PET/CT showed that the maximum standardized uptake value (SUVmax) of intrahepatic lesions was reduced to 62.14%. Abdominal MRI revealed that the sum of target lesion diameters was less than 30% that at baseline. PERCIST indicated partial metabolic response, whereas RECIST suggested stable disease. Conclusion: FDG PET/CT-based PERCIST may be accurate in determining treatment response and evaluating patient prognosis after DEBIRI-TACE in unresectable CRLM.